GE_GERICHTE P/14034/2019 vom 27. April 2021 - GE Cour de justice (2021)
RECOURS JOINT;FIXATION DE LA PEINE;TRAITEMENT AMBULATOIRE;EXPULSION(DROIT PÉNAL);CAS DE RIGUEUR | CPP.400.al2; CP.47; CP.61.al1; CP.63.al1; CP.66A.al2